Migrant workers' access to remedy for exploitation in Australia: the role of the national Fair Work Ombudsman. Issue 3 (2nd September 2017) - Farbenblum, Bassina; Berg, Laurie
ABSTRACT: Exploitation of temporary migrant workers in Australia has emerged as a significant human rights concern. However, limited attention has been paid to the State's responsibility to ensure individual workers can access remedies for rights violations. This article considers whether Australia's government agencies and institutional frameworks are suitable to enabling remedies for temporary migrant workers, and how well they deliver remedies to individuals in practice. Drawing on new empirical data, it focuses on the role of the national labour inspectorate, th Fair Work Ombudsman (FWO). FWO has undertaken various education, compliance and deterrence initiatives directed to systemically improving conditions for migrant workers. This article considers the extent to which individual migrant workers seek assistance from FWO to recover their personal unpaid wages, and the remedial outcomes of individual claims lodged with the agency. We illuminate structural factors contributing to migrants' reluctance to engage with FWO, as well as factors contributing to low wage recovery rates for those who do contact FWO. We conclude that although these challenges are numerous and multi-layered, they are not all inevitable. Reforms should incorporate a new migrant-centred approach that recalibrates the risks and costs of seeking remedies against the likelihood of obtaining a just outcome.